Social networks on the internet in high school - between mutual learning and school knowledge - Paulo Cesar Rodrigues Carrano (Universidade Federal de Santa Catarina, 2017)
The article is the result of a case study that used a quantitative and qualitative methodological approach, in a public high school in Rio de Janeiro. It contextualizes the education of youth in relation to societal changes using as references authors who look at sociology at an individual scale and processes of autonomization and youth educational experiences. The study was conducted in two stages. In the first, we issued a structured questionnaire to 1,224 students and 44 teachers. In the second stage we conducted individual and group interviews involving teachers and students. We sought to understand the presence of internet social networks in everyday school life and their use by teachers and students. The data allowed broadening understanding of the multiple interactions, conflicts and convergences between the subjects of the school based on the mediations of these networks. Differentiated interactions between teachers and students were found as well as different levels of skills among teachers and students. Faced with social networks, teachers express practices that have still not succeeded to reconfigure the Pedagogical Policy Project of the school studied.